2018
DOI: 10.1159/000487034
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of the Innate Immune Receptor TLR10 in Obesity and Type-2 Diabetes: Association with ROS-Mediated Oxidative Stress

Abstract: Background/Aims: Metabolic diseases such as obesity and type-2 diabetes (T2D) are known to be associated with chronic low-grade inflammation called metabolic inflammation together with an oxidative stress milieu found in the expanding adipose tissue. The innate immune Toll-like receptors (TLR) such as TLR2 and TLR4 have emerged as key players in metabolic inflammation; nonetheless, TLR10 expression in the adipose tissue and its significance in obesity/T2D remain unclear. Methods: TLR10 gene expression was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 50 publications
4
52
0
3
Order By: Relevance
“…In line with this finding, increased expression of TLRs 1-9 and TLRs 11-13 was reported in two murine models of obesity [55]. Whereas in obese/T2D individuals, we have already reported the increased expression of several TLRs including TLR-2, -4, -7, -8, and -10 [28,[56][57][58]. The present data show the congruence between adipose tissue expression of IRF5 and most TLRs in obesity/T2D.…”
Section: Discussionsupporting
confidence: 91%
“…In line with this finding, increased expression of TLRs 1-9 and TLRs 11-13 was reported in two murine models of obesity [55]. Whereas in obese/T2D individuals, we have already reported the increased expression of several TLRs including TLR-2, -4, -7, -8, and -10 [28,[56][57][58]. The present data show the congruence between adipose tissue expression of IRF5 and most TLRs in obesity/T2D.…”
Section: Discussionsupporting
confidence: 91%
“…Low concentration of ROS is permanently produced in cells, which plays a role as signal molecules. Researches show that ROS participate in the production of many inflammatory cytokines by the different signal pathways such as MAPK and NF-κB [37, 38]. In the study, we found that FPA stimulated the production of superoxide anion in VSMCs, and the NADPH oxidase inhibitor DPI, mitochondrial respiratory complex II inhibitor TTFA and antioxidant NAC all inhibited FPA-induced the generation of superoxide anion in VSMCs, suggesting that the NADPH oxidase pathway and mitochondria-derived signal pathway are involved in FPA-elicited ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…In consensus with such inflammatory signatures and immune activation, elevated AT expression of TLR8 has been also reported in metabolically compromised subjects [30]. Finally, TLR10 has been considered the only orphan human TLR, with no confirmed ligand nor biological function until the findings of Song Jiang and coworkers, supporting the idea that TLR10 may display some anti-inflammatory properties [31], and the approach recently performed in human AT by Syndhu et al [32], suggestive of a relationship with metabolic inflammation.…”
Section: Introductionmentioning
confidence: 88%